Dynamic patterns of particulate matter concentration and size distribution in urban street canyons: insights into diurnal and short-term seasonal variations - Wang, X.; Chen, X.; Zhou, Z.; Teng, M.; Xiang, Y.; Peng, C.; Huang, C.; Peng, C. (Environmental Monitoring and Assessment, 2024)

Future soil organic carbon stocks in China under climate change - Wu, J.; Liu, S.; Peng, C.; Luo, Y.; Terrer, C.; Yue, C.; Peng, S.; Li, J.; Wang, B.; Shangguan, Z.; Deng, L. (Cell Reports Sustainability, 2024)

Impacts of Urbanization on Economic Development and Ecological Protection of the Wuhan City Circle, China - Li, Y.; Huang, C.; Liu, S.; Cheng, J.; Xiang, Y.; Peng, C. (Land Degradation and Development, 2024)

Vulnerability of barley yields in Québec - Epule Epule, T.; Poirier, V.; Peng, C.; Etongo, D. (Environmental Monitoring and Assessment, 2024)

Shifts in Plant Phenology Significantly Affect the Carbon Allocation in Different Plant Organs - Ren, P.; Li, P.; Zhou, X.; Liu, Z.; Tang, J.; Zhang, C.; Zou, Z.; Li, T.; Peng, C. (Ecology Letters, 2024)

Balancing Water Yield and Water Use Efficiency Between Planted and Natural Forests: A Global Analysis - Sun, S.; Xiang, W.; Ouyang, S.; Hu, Y.; Peng, C. (Global Change Biology, 2024)

Observed Vertical Dispersion Patterns of Particulate Matter in Urban Street Canyons and Dominant Influencing Factors - Wang, X.; Chen, X.; Ma, B.; Zhou, Z.; Peng, C. (Forests, 2024)

Characteristics of Meteorological Drought Evolution in the Yangtze River Basin - Bai, W.; Zhang, C.; Xiao, X.; Zou, Z.; Liu, Z.; Li, P.; Tang, J.; Li, T.; Zhou, X.; Peng, C. (Water (Switzerland), 2024)

Long-term nitrogen addition has a positive legacy effect on soil respiration in subtropical Moso bamboo forests - Li, Q.; Zhang, C.; Shi, M.; Lv, J.; Peng, C.; Zhang, J.; Chang, S.X.; Cao, T.; Li, T.; Song, X. (Geoderma, 2024)

Nocturnal peak methane flux diel patterns in rice paddy fields - Li, H.; Peng, C.; Helbig, M.; Zhao, M.; Guo, H.; Zhao, B. (Agricultural and Forest Meteorology, 2024)

Drought and warming interaction cause substantial economic losses in the carbon market potential of China's northern grasslands - Guo, J.; Li, T.; Wu, T.; Wang, Z.; Zou, Z.; Peng, C.; Zhou, X.; Li, P.; Liu, Z.; Tang, J.; Zhang, C. (Science of the Total Environment, 2024)

Biochar amendment alleviates soil microbial nitrogen and phosphorus limitation and increases soil heterotrophic respiration under long-term nitrogen input in a subtropical forest - Li, Q.; Ji, H.; Zhang, C.; Cui, Y.; Peng, C.; Chang, S.X.; Cao, T.; Shi, M.; Li, Y.; Wang, X.; Zhang, J.; Song, X. (Science of the Total Environment, 2024)

Estimating wetland CH4 emissions on the Qinghai-Tibetan Plateau based on a processed model coupled with inundation dynamics between 1960 and 2100 - Zhang, J.; Chen, H.; Peng, C.; Huang, Y.; Wang, Y.; Liu, X.; Wang, M.; Wang, L.; Yu, D.; Zhu, Q. (Science of the Total Environment, 2024)

Global riverine land-to-ocean carbon export constrained by observations and multi-model assessment - Liu, M.; Raymond, P.A.; Lauerwald, R.; Zhang, Q.; Trapp-Müller, G.; Davis, K.L.; Moosdorf, N.; Xiao, C.; Middelburg, J.J.; Bouwman, A.F.; Beusen, A.H.W.; Peng, C.; et al. (Nature Geoscience, 2024)

Cold‐Season Methane Fluxes Simulated by GCP‐CH4 Models - Ito, A.; Li, T.; Qin, Z.; Melton, J. R.; Tian, H.; Kleinen, T.; Zhang, W.; Zhang, Z.; Joos, F.; Ciais, P.; Hopcroft, P. O.; Beerling, D. J.; et al. (Geophysical Research Letters, 2023)
Abstract Cold‐season methane (CH 4 ) emissions may be poorly constrained in wetland models. We examined cold‐season CH 4 emissions simulated by 16 models participating in the Global Carbon Project model intercomparison and analyzed temporal and spatial patterns in simulation results using prescribed inundation data for 2000–2020. Estimated annual CH 4 emissions from northern (>60°N) wetlands averaged 10.0 ± 5.5 Tg CH 4 yr −1 . While summer CH 4 emissions were well simulated compared to in‐situ flux measurement observations, the models underestimated CH 4 during September to May relative to annual total (27 ± 9%, compared to 45% in observations) and substantially in the months with subzero air temperatures (5 ± 5%, compared to 27% in observations). Because of winter warming, nevertheless, the contribution of cold‐season emissions was simulated to increase at 0.4 ± 0.8% decade −1 . Different parameterizations of processes, for example, freezing–thawing and snow insulation, caused conspicuous variability among models, implying the necessity of model refinement. , Plain Language Summary Wetlands in the northern high latitudes are a major source of methane (CH 4 ) to the atmosphere, mainly during the warm season. Previously, models have assumed that cold‐season CH 4 emissions are low, but recent observations suggest high‐latitude wetlands can be substantial sources even in winter. We compared CH 4 emissions simulated by 16 state‐of‐the‐art wetland models, participating in a model intercomparison project with a focus on the cold‐season in northern wetlands. The model simulations indicated that nearly one third of annual emissions were simulated to occur from September to May, and CH 4 emissions to the atmosphere were not negligible even under freezing air temperatures, although the results differed greatly among the models. However, field studies suggest cold‐season emissions account for an even larger fraction of annual emissions. These results highlight the contribution of cold‐season emissions to the annual CH 4 budget, which future climatic warming is expected to affect severely, and they also show that simulations of cold‐season CH 4 emissions from wetlands need to be improved. , Key Points Cold‐season methane (CH 4 ) emissions simulated by 16 Global Carbon Project‐CH 4 wetland models were analyzed Most models underestimate the cold‐season emissions in comparison with observational data Further model improvement by including cold‐season processes is required to reduce the model bias and uncertainty

Critical needs to close monitoring gaps in pan-tropical wetland CH4 emissions - Zhu, Q.; Yuan, K.; Li, F.; Riley, W.J.; Hoyt, A.; Jackson, R.; McNicol, G.; Chen, M.; Knox, S.H.; Briner, O.; Beerling, D.; Gedney, N.; et al. (Environmental Research Letters, 2024)